Entre mortificações e resistências : a saúde e o psicotrópico no sistema prisional - Freitas, Mariana Moulin Brunow (2013)
The health and the use of psychotropic in the prison system live in paradox. The penitentiary system, during the last decades, passed through some transformations. In the world, the statistics indicate the rise of prison population and the overcrowded situation, without respectful conditions to live. In Brazil, conditions are the same: the prison population during the last ten years duplicated, the conditions of confinement are very poor and infectious diseases are very common. In front of this reality, in 2003 was approved the National Health Plan in the Prison System (NHPPS), in concord with Unified Health System, try to improve the integrality and universality health access to the prisoners. In Espírito Santo state adhered NHPPS and created the Operating State Plan of Integral Health Care of Prison Population (2004), nevertheless, only in 2010 the access to the prison health service became reality. In this context, the research of this master’s degree tried to investigate the practices of health in prisional system and the way the psychotropic drugs can be used by prisoners in Maximum Security Prison II (MASP II), located in Viana, Espírito Santo. Therefore, it was necessary to habit the prison system and to carry out interviews with professionals in the management of prison healthcare from the State Department of Justice of Espírito Santo, with psychiatric professional and prisoners of MASP II. Thus, it was possible to observe that health in the prison system, as well as the uses of psychotropic drugs, are in a porous space. The healthcare practices can fortify strategies of control and produce mortification, as they can escape from biopolitics investments and produce resistance. The use of psychotropic by the inmates is in ambivalence: they can be adjusters’ instruments of capture, as they can produce autonomy by the prisoners on their use. Finally, between mortification and resistances, is the prisoner who manages the tensions of this paradox and will produce life, powerful life.